Fatty acid recycling in adipocytes: a role for glyceroneogenesis and phosphoenolpyruvate carboxykinase. (1st December 2003) - Forest, C.; Tordjman, J.; Glorian, M.; Duplus, E.; Chauvet, G.; Quette, J.; Beale, E.G.; Antoine, B.
Abstract : FA (fatty acid) recycling in adipose tissue appears to be an important pathway for regulating FA release into the blood during fasting. Re-esterification requires G3P (glycerol 3-phosphate), which cannot be synthesized from glucose because glycolysis is much reduced under such circumstances. In addition, G3P can scarcely originate from glycerol since glycerol kinase has a very low activity in white adipose tissue. It was shown about 35 years ago that a metabolic pathway named glyceroneogenesis, which allows G3P synthesis from non-carbohydrate precursors like pyruvate, lactate or amino acids, is activated during fasting. The major enzyme in this pathway was shown to be PEPCK-C [cytosolic phosphoenolpyruvate carboxykinase (GTP); EC 4.1.1.32]. The present review analyses the mechanisms by which a series of hormones and nutrients affect PEPCK-C gene transcription and glyceroneogenesis and describes evidence for dysregulation of this pathway in type 2 diabetes.